Quantitative and qualitative deficits in neonatal lung-migratory dendritic cells impact the generation of the CD8+ T cell response. - Tracy J Ruckwardt; Allison M W Malloy; Kaitlyn M Morabito; Barney S Graham (PLoS Pathogens, 2014)
CD103+ and CD11b+ populations of CD11c+MHCIIhi murine dendritic cells (DCs) have been shown to carry antigens from the lung through the afferent lymphatics to mediastinal lymph nodes (MLN). We compared the responses of these two DC populations in neonatal and adult mice following intranasal infection with respiratory syncytial virus. The response in neonates was dominated by functionally-limited CD103+ DCs, while CD11b+ DCs were diminished in both number and function compared to adults. Infecting mice at intervals through the first three weeks of life revealed an evolution in DC phenotype and function during early life. Using TCR transgenic T cells with two different specificities to measure the ability of CD103+ DC to induce epitope-specific CD8+ T cell responses, we found that neonatal CD103+ DCs stimulate proliferation in a pattern distinct from adult CD103+ DCs. Blocking CD28-mediated costimulatory signals during adult infection demonstrated that signals from this costimulatory pathway influence the hierarchy of the CD8+ T cell response to RSV, suggesting that limited costimulation provided by neonatal CD103+ DCs is one mechanism whereby neonates generate a distinct CD8+ T cell response from that of adults.